The origins of postmodernity - Anderson, Perry (Verso, 2006)
Where does the idea of the postmodern come from? Who first conceived, and who developed it? How have its meanings changed? What purposes do they serve? These are the questions addressed in The Origins of Postmodernity. The answers take us from Lima to Angkor, to Paris and Munich, to China and the stars. At the center of the story is the figure of Fredric Jameson, theorist supreme of postmodernism. What happens to art, time, politics, in the age of the spectacle? What has ended, and what has begun?